A Graphical Query Generator for Clinical Research Databases - Banhart, F.; Klaeren, H. (Methods of Information in Medicine, 1995)
Clinical research involves recording, storage and retrieval of disease-related patient data, typically using a database system. In order to facilitate ad hoc queries to clinical databases we have developed a query generator with a graphical interface. The query generator uses an object-oriented data model which is visualized by directed graphs. The main focus of our work was the definition of object-oriented user views to the partly complex data structures of a relational database. Furthermore, we tried to define graphical abstractions for all common types of queries. Thus, even for non-expert database users such as clinicians, it is easy to assemble highly complex queries for a thorough examination of the content of large research databases.
Keywords: Graphical Query Languages; Object-Oriented Data Models; Database Management Systems; Clinical Research; Medical Information Systems